Implementasi Nadhom Jurumiyah Jawan Karya KH. Muhammad Adnan dalam Pembelajaran Nahwu Santri Kelas 1 Wustho Madrasah Diniyah Tri Bhakti At-Taqwa Lampung Timur - Nur Alimah; Asep Sunarko; H. Ngatoillah Linnaja; Mustahar Ali Wardana (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to: 1) Find out the implementation of nahwu learning with Naz>am Juru>miyyah Ja>wa>n by KH. Muhammad Adnan, student of class 1 wusta Madrasah Diniyah Tri Bhakti At-Taqwa, East Lampung. 2) Knowing the supporting and inhibiting factors for the implementation of Nazam Juru>miyyah Ja>wa>n in the learning of nahwu santri class 1 wusta Madrasah Diniyah Tri Bhakti At-Taqwa East Lampung. 3) Knowing the nahwu learning evaluation system with Nazam Juru>miyyah Ja>wa>n by KH. Muhammad Adnan, student of class 1 wusta Madrasah Diniyah Tri Bhakti At-Taqwa, East Lampung.This research uses a qualitative approach where the type of research is field research. Data collection techniques use observation, interviews and documentation methods. The analysis techniques used are data reduction, data presentation and drawing conclusions.The results of this research show that: 1) Implementation of nahwu learning with Nazam Juru>miyyah Ja>wa>n, namely that students are given an explanation of the material with examples and then instructed to look for other examples that match the material and explain the rules of nahwu, students are required to memorize nazaman with a target of 2 semesters. 2) Supporting factors for learning nahwu using Nazam Juru>miyyah Ja>wa>n are students having books with translations of other nahwu books, reading every time they start learning, requirements for taking the semester/final exam with the Qiroatul Polar exam, the graduation of students who are finish nazaman deposit. The inhibiting factor is the lack of classroom learning hours, students need to adapt to the boarding school environment. 3) The nahwu learning evaluation system with Nazam Juru>miyyah Ja>wa>n orally, students are instructed to read the book Fathul Qari>b then ask questions about the rules of nahwu. In writing, it is carried out during the odd and final semester exams.